(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2020)
INTRODUCTION:Myofunctional therapy starts as an original and innovative treatment option, non-occupying, and easy to adapt, so the question arises of the effectiveness of this therapy and its exercises which have allowed the evolution of the patient. METHODS:A systematic review of the literature that collects several scientific studies that generate hypotheses was carried out, answering some questions through the Cochrane systematic review, the organization of these questions that follow the PICO questions framework, by selecting articles with the PRISMA methodology RESULTS:This review allowed to demonstrate the effectiveness of myofunctional therapy in patients with facial paralysis; The articles were screened and included for selection following the PRISMA diaphragm, showing 180 articles, of which 60 were discarded for not presenting the inclusion requirements embodied in the investigation. ANALYSIS AND DISCUSSION:The data analysis shows that myofunctional therapy offers an alternative treatment in cases of facial paralysis through stimulation exercises that provide adequate evolution in patients. CONCLUSIONS:Research provides the efficacy of myofunctional exercises as an easily accessible and effective treatment.